A triple-band frequency selective surface for 5G millimeter-wave communications - Gurdal, Senanur; Aksimsek, Sinan; Tokan, Nurhan T. (WILEY, 2023)
In this letter, a new triple-band millimeter-wave frequency selective surface (FSS) is presented. The proposed FSS structure consists of three slot-based resonance mechanisms on the single layer of Rogers Diclad880 dielectric. It shows a high compactness with a unit cell surface area of 5.4 x 5.4 mm(2). The proposed FSS exhibits a triple-band bandpass filter characteristics for the allocated 5G millimeter-wave frequency regions with sufficient bandwidths corresponding to 23.5-24.6, 27-28.5, and 37.5-41 GHz, respectively. Simulation outcomes reveal that the FSS poses polarization insensitive behavior, and maintains high transmission skill for a wide range of incident angles up to 40 degrees. A 40 x 40 FSS panel is fabricated, and the experimental verification is carried out. The outcomes prove that the proposed FSS is suitable for multiband 5G millimeter-wave filtering applications.
Keywords: 5G communications; bandpass filter; frequency selective surface; millimeter-waves; triple bandpass; FSS; DESIGN; WINDOW; Engineering; Optics